Smallholder farmers' perceptions on climate change and the use of sustainable agricultural practices in the chinyanja triangle, Southern Africa - Makate, C.; Makate, Marshall; Mango, N. (M D P I AG, 2017)
© 2016 by the author. In developing regions with high levels of poverty and a dependence on climate sensitive agriculture, studies focusing on climate change adaptation, planning, and policy processes, have gained relative importance over the years. This study assesses the impact of farmer perceptions regarding climate change on the use of sustainable agricultural practices as an adaptation strategy in the Chinyanja Triangle, Southern Africa. In this empirical approach, we adopt methods that account for the plausibility that unmeasured characteristics exist, which are correlated with perceptions and the adoption of Sustainable Agricultural Practices. We use a unique and representative dataset collected in December 2012 and June 2013, from smallholder farmers in the Chinyanja Triangle. The results indicate that farmer's perceptions significantly influence the use of sustainable agricultural practices. Specifically, we established that farmer perceptions considerably impact the use of grain legume rotations, inorganic fertilizers, compost, and farmyard manure. Our results highlight the need for a serious and perhaps equal consideration of farmer perceptions regarding climate change, as important inputs to climate change adaptation policies targeted at enhancing climatic resilience in smallholder farming communities. This is plausible as the adaptation and pliability of farmers to the effects of climate change should be a social process involving the collective efforts from various stakeholders.